Cooperation and crosstalk in axon guidance cue integration: Additivity, synergy, and fine‐tuning in combinatorial signaling. Issue 7 (26th October 2016) - Morales, Daniel; Kania, Artur
ABSTRACT: Neural circuit development involves the coordinated growth and guidance of axons to their targets. Following the identification of many guidance cue molecules, recent experiments have focused on the interactions of their signaling cascades, which can be generally classified as additive or non‐additive depending on the signal convergence point. While additive (parallel) signaling suggests limited molecular interaction between the pathways, non‐additive signaling involves crosstalk between pathways and includes more complex synergistic, hierarchical, and permissive guidance cue relationships. Here the authors have attempted to classify recent studies that describe axon guidance signal integration according to these divisions. They also discuss the mechanistic implications of such interactions, as well as general ideas relating signal integration to the generation of diversity of axon guidance responses. © 2016 Wiley Periodicals, Inc. Develop Neurobiol 77: 891–904, 2017